Hypofractionated radiotherapy for complicated bone metastases in patients with poor performance status: a phase II international trial. Issue 2 (April 2019) - Silva, Mauricio F.; Marta, Gustavo N.; Lisboa, Felipe P.C.; Watte, Guilherme; Trippa, Fabio; Maranzano, Ernesto; da Motta, Neiro W.; Popovic, Marko; Ha, Tuan; Burmeister, Bryan; Chow, Edward
Purpose: To evaluate the efficacy and safety of hypofractionated radiotherapy (16 Gy in 2 fractions, 1 week apart) in patients with complicated bone metastases and poor performance status. Methods: A prospective single-arm phase II clinical trial was conducted from July 2014 to May 2016. The primary endpoint was pain response as defined in the International Consensus on Palliative Radiotherapy Endpoints. Secondary endpoints included quality of life as measured by quality of life questionnaire (QLQ) PAL-15 and QLQ-BM22 European Organisation for Research and Treatment of Cancer guidelines, pain flare, adverse events, re-irradiation, and skeletal complications. Results: Fifty patients were enrolled. There were 23 men with a median age of 58 years (range 26-86). Of the 50 patients, 38 had an extraosseous soft tissue component, 18 needed postsurgical radiation, 3 had neuropathic pain, and 3 had an impending fracture in a weight-bearing bone. At 2 months, 33 patients were alive (66%). Four (12.5%) had a complete response and 12 (37.5%) had a partial response. A statistically significant improvement was seen in the functional interference (p = 0.01) and psychosocial aspects (p = 0.03) of the BM22. No patient had spinal cord compression. One patient required surgery for pathologic fracture, and another re-irradiation. Conclusions: Hypofractionated radiotherapy (16 Gy in 2 fractions of 8 Gy 1 week apart) achieved satisfactory pain relief and safety results in patients with complicated bone metastases and poor performance status.